Joint Waveform and Filter Design for Interference Suppression in Moving Target Environments - Lan, Zhengyu; Zuo, Lei; Liao, Bin; Yang, Tian (IEEE transactions on aerospace and electronic systems, 2025)
Moving targets and digital radio frequency memory (DRFM) interference distort the radar echo due to complex waveform modulation, severely degrading the radar detection performance. In this article, we propose a joint waveform and filter design scheme with Doppler-tolerant and antijamming (JWFDA) for DRFM interference suppression in moving target environments. First, we formulate the moving target autocorrelation peak sidelobe level (M-APSL) model of moving target clusters and the moving jamming cross-correlation peak level (M-JCPL) model of DRFM interference. Second, we establish a JWFDA design scheme to simultaneously minimize M-APSL and M-JCPL while satisfying the moving target loss in processing gain constraint of transmit waveform and receive filter, which is a nonconvex, nonsmooth, and multimax function optimization problem. To solve it, we smooth the multimax function by using the L_{p} norm. Third, we propose a multi- L_{p} norm balanced penalty majorization-minimization algorithm, which approximates the multi- L_{p} norm as a quadratic polynomial and avoids the overfitting of penalty terms. Numerical simulations demonstrate that the proposed method generates the waveforms and the filters with superior performance and effectively suppresses several kinds of DRFM interference in moving target environments.